2019
DOI: 10.1186/s12889-019-6640-5
|View full text |Cite
|
Sign up to set email alerts
|

Coaching and/or education intervention for parents with overweight/obesity and their children: study protocol of a single-centre randomized controlled trial

Abstract: Background In Canada, a majority of children and adults are insufficiently active for health gains, and about one in seven children and over 20% of adults are overweight or obese. Overweight and obesity are risk factors for many chronic diseases in both adults and children and can result in lower quality and quantity of life. Children whose parents are overweight or obese are more likely to become overweight themselves. Thus, parent/child interventions are important for reducing obesity and promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 71 publications
(87 reference statements)
1
23
0
2
Order By: Relevance
“…While the researchers reported no statistically significant difference in PA engagement, they noted that 16 of their 19 participants achieved weight loss, resulting in significant BMI reductions over the course of the intervention [ 66 ]. These downward trends have been noted in previous studies in which the researchers found that individualized CALC interventions can produce significant BMI reductions [ 41 , 66 , 67 ]. For instance, Pearson and colleagues [ 38 ] assessed the effectiveness of two self-management approaches on obesity via a 12-week telephone-based intervention in which one group received MI-via-CALC while the other received a structured lifestyle program.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…While the researchers reported no statistically significant difference in PA engagement, they noted that 16 of their 19 participants achieved weight loss, resulting in significant BMI reductions over the course of the intervention [ 66 ]. These downward trends have been noted in previous studies in which the researchers found that individualized CALC interventions can produce significant BMI reductions [ 41 , 66 , 67 ]. For instance, Pearson and colleagues [ 38 ] assessed the effectiveness of two self-management approaches on obesity via a 12-week telephone-based intervention in which one group received MI-via-CALC while the other received a structured lifestyle program.…”
Section: Discussionsupporting
confidence: 71%
“…Ethical approval was received from the host institution’s Health Sciences’ Research Ethics Board (ID# 109219). The methods pertaining to the protocol and a complete intervention description have been published elsewhere [ 41 ]. However, as the current study progressed some necessary adjustments were made to the protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the proximity of the parent-child relationship and many published papers on the importance of the parent-child dyad [32][33][34][35], there is a range of identified barriers to parents engaging in the promotion of health with children. Parent concerns about safety have been identified as a central and consistent barrier to physical activity participation of children [36].…”
Section: Introductionmentioning
confidence: 99%
“…Health coaching uses a supportive relational framework to encourage the development of autonomous choice, strength, confidence, readiness, and motivation to change. 22,23 The coaching skills employed in such a framework include the principles of positive psychology and positivity, 24 practices of gratitude, recognition of small steps and small change, appreciative inquiry, 25 mindfulness, "SMART" (specific, measurable, attainable, relevant, and timely) goal setting, 26 and the use of "desire to change" and "confidence to change" scales. 27 When required to manage ambivalencemotivational interviewing and decisional balance interventions may be used.…”
Section: A Proposed Health Coaching Approach To Support Behavior Chanmentioning
confidence: 99%